Peran UMKM Omah Bawis Pak Ucil Terhadap Kesejahteraan Masyarakat Dalam Perspektif Ekonomi Islam (Studi Kasus UMKM Omah Bawis Pak Ucil), - Magfirah, Adia; Parno, Parno; Yusran, Yusran (Borneo Islamic Finance and Economics Journal, 2023)
Adia Magfirah,2023."The Role of UMKM Omah Bawis Pak Ucil on Community Welfare in an Islamic Economic Perspective (Case study of UMKM Omah Bawis Pak Ucil), Thesis, Islamic Economics and Business Study Program Department of Sharia Economics Sultan Aji Muhammad Idris State Islamic University Samarinda". This research was supervised by Mr. Parno, M.SI as supervisor I and Mr. H. Yusran M. Ag as supervisor II. The background of this study is that welfare is one of the conditions where a person can meet basic needs, food, shelter, and the ability to continue education and https://www.fortyouncewines.com/ have additional jobs. For business actors, UMKM are businesses run by individuals, households, and small business entities. The purpose of this study is to find out how the role of UMKM in the welfare of the community is carried out in UMKM Omah Bawis Pak Ucil. This research is a field research using a qualitative descriptive approach, using data collection techniques used are observation, interviews and documentation. The data sources used are primary data and secondary data. Primary data sources through interviews obtained through interviews with UMKM owners Omah Bawis and the community. While secondary data sources are obtained from relevant books and journals. The data analysis techniques used are data analysis techniques from Miles, Huberman, and Saldana. While the data validity technique used is triangulation of source and time. The location of this research used is the Omah Bawis Bontang UMKM Production House on June 3, 2023. The results of this study show that this is the role of UMKM in the Omah Bawis fisheries sector on community welfare. Viewed in terms of production which includes the provision and creation of something that is valuable and beneficial to society in the form of goods and services. The business, run by entrepreneur Omah Bawis Pak Ucil, aims to improve the family economy in the Bontang City community.